1 IRELAND. (July 2022) - Unknown
Abstract : The Liberal peer and Lord Lieutenant of Ireland encourages Lord Londonderry, as Lord Lieutenant of County Down, to appoint two 'political opponents' to the vacant positions of Deputy Lieutenant for County Down.